Postural Balance in Individuals With Knee Osteoarthritis During Stand-to-Sit Task - Fu, Shengxing; Duan, Tingjin; Hou, Meijin; Yang, Fengjiao; Chai, Yatai; Chen, Yongkang; Liu, Benke; Ma, Ye; Liu, Anmin; Wang, Xiangbin; Chen, Lidian (Frontiers in Human Neuroscience, 2021)
Objective: Stand-to-sit task is an important daily function, but there is a lack of research evidence on whether knee osteoarthritis (knee OA) affects the postural balance during the task. This study aims to compare individuals with knee OA and asymptomatic controls in postural balance and identify kinematic and lower extremity muscle activity characteristics in individuals with knee OA during stand-to-sit task. Methods: Thirty individuals with knee OA and thirty age-matched asymptomatic controls performed the 30-second Chair Stand test (30sCST) at self-selected speeds. Motion analysis data and surface electromyography (sEMG) were collected while participants performed the 30sCST. To quantify postural balance, the displacement of the center of mass (CoM) and peak instantaneous velocity of the CoM were calculated. The kinematic data included forward lean angles of the trunk and pelvic, range of motion (RoM) of hip, knee and ankle joints in the sagittal plane. The averaged activation levels of gluteus maximus (GMAX), vastus lateralis (VL), vastus medialis (VM), rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA) and medial head of gastrocnemius (MG) muscles were indicated by the normalized root mean square (RMS) amplitudes. Results: Compared with asymptomatic control group, knee OA group prolonged the stand-to-sit task duration, demonstrated significantly larger CoM displacement and peak instantaneous CoM velocity in the anterior-posterior direction, reduced ankle dorsiflexion RoM, greater anterior pelvic tilt RoM, lower quadriceps femori and muscles activation level coupled with higher BF muscle activation level during stand-to-sit task. Conclusion: This research indicates that individuals with knee OA adopt greater pelvic forward lean RoM, higher BF muscle activation level during stand-to-sit task. However, these individuals still exist greater CoM excursion in the anterior-posterior direction and take more time to complete the task. This daily functional activity should be added to the rehabilitation goals for individuals with knee OA. Knee OA group performs reduced ankle dorsiflexion RoM, quadriceps femoris and TA activation deficit. In the future, rehabilitation programs targeting these impairments could be beneficial for restoring the functional transfer in individuals with knee OA.